2001
DOI: 10.1086/322673
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis of Coagulase‐NegativeStaphylococcusIsolates from Blood Cultures: Prevalence of Genotypic Variation and Polyclonal Bacteremia

Abstract: Fifty-seven coagulase-negative Staphylococcus isolates from 22 inpatients who had > or =2 blood cultures that were positive for Staphylococcus within 24 hours were analyzed to determine the frequency of polyclonal bacteremia. Patients were considered to have bacteremia (14 patients) or contamination of sample (8 patients) on the basis of clinical criteria. Nine colonies were randomly selected from each blood culture and genotyped by means of SmaI digestion/pulsed-field gel electrophoresis. Relatedness was dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
30
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 25 publications
2
30
0
Order By: Relevance
“…Another difficulty in phenotypic microbiological characterization of CNS CR-BSI is the differentiation of morphotypes after incubation periods shorter than 48 h. Different morphotypes are frequently observed after only 72 h of incubation and frequently reflect differences at the genotypic level (11,12,17,23,25,29,33). The possibility of a sampling error in phenotypic diagnosis when a single colony of the culture is being studied may be high (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another difficulty in phenotypic microbiological characterization of CNS CR-BSI is the differentiation of morphotypes after incubation periods shorter than 48 h. Different morphotypes are frequently observed after only 72 h of incubation and frequently reflect differences at the genotypic level (11,12,17,23,25,29,33). The possibility of a sampling error in phenotypic diagnosis when a single colony of the culture is being studied may be high (24).…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between species identification, even including biotypes with typing characterization by genotypic methods (e.g., PFGE), is largely imprecise (15). At the same time, the determination of the sensitivity pattern as a typing method is also inaccurate (13,17,22,23,31).Another difficulty in phenotypic microbiological characterization of CNS CR-BSI is the differentiation of morphotypes after incubation periods shorter than 48 h. Different morphotypes are frequently observed after only 72 h of incubation and frequently reflect differences at the genotypic level (11,12,17,23,25,29,33). The possibility of a sampling error in phenotypic diagnosis when a single colony of the culture is being studied may be high (24).…”
mentioning
confidence: 99%
“…PFGE analysis has been used by several researchers to assess strain relatedness and to determine the significance of CoNS isolated from multiple blood cultures (9,21). Two recent studies have shown that fewer than half of the patients with two or more blood cultures positive for CoNS had the same strain (8,20).…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been reported that 6 to 21% of true bacteremia cases represent polymicrobial infections (17,35). None of the current methods used to determine species or strain identity are capable of direct identification of polymicrobial infections; subculture of the clinical sample is necessary.…”
Section: Discussionmentioning
confidence: 99%